Prevalence of oral impacts on daily performances (OIDP) of elderly people in Curitiba – PR - Lígia Moura Burci; Yasmin Dallarmi Miguel; Obdulio Gomes Miguel; Astrid Wiens Souza; Josiane de Fátima Gaspari Dias; Marilis Dallarmi Miguel (Brazilian Dental Science)
This study aimed to investigate the prevalence of oral health impact on the daily performance of Brazilian elderly, living in the city ofCuritiba – PR. The oral health-related quality of life (OHRQoL) of 129 elderly people aged from 60 to 80 years was assessed. Also, the influence of gender, income, attendance to the dentist, self-assessment of health, and social-demographic features were verified. Oral health influenced in 83.72%the daily routine of the participants. The lack of compliance to dental treatment and the difficulty in oral health self-perception as integrate part of general health were associated to the greatest interference.Thus, we recommended that the self-perception of the individuals is considered simultaneously to the clinical condition to tailor oral health actions targeted to priority groups.